Activation of peroxisome proliferator–activated receptor gamma induces anti-inflammatory properties in the chicken free avian respiratory macrophages - Mutua, Mbuvi P.; Steinaa, Lucilla; Shadrack, Muya M.; Muita, Gicheru M. (Springer, 2015)
Activation of peroxisome proliferator activated receptor gamma (PPAR γ) in the alveolar macrophages (AM) by selective synthetic PPAR γ ligands, improves the ability of the cells to resolve inflammation. In birds, respiratory macrophages are known as free avian respiratory macrophages (FARM) and show distinct functional differences from AM. The effects of treating FARM with PPAR γ ligands are unclear.FARM were harvested by lavage of chicken respiratory tract and their morphology assessed at microscopic level. The effects of PPAR γ agonists on the FARM in vitro viability, phagocytic capacity and proinflammatory cytokine (TNF-α) production were assessed.FARM had eccentric nucleus and plasma membrane ruffled with filopodial extensions. Ultrastructurally, numerous vesicular bodies presumed to be lysosomes were present. FARM treated with troglitazone, a selective PPAR γ agonist, had similar in vitro viability with untreated FARM. However, treated FARM co-cultured with polystyrene particles, internalized more particles with a mean volume density of 41 % compared to that of untreated FARM of 21 %. Further, treated FARM significantly decreased LPS-induced TNF-α production in a dose dependent manner.Results from this study show that PPAR γ synthetic ligands enhance phagocytic ability of FARM. Further the ligands attenuate production of proinflammatory cytokines in the FARM, suggesting potential therapeutic application of PPAR γ ligands in the management of respiratory inflammatory disorders in the poultry industry.